Primary treatment of type B post-axial ulnar polydactyly: A systematic review and meta-analysis. (December 2022) - Samarendra, Harsh; Wade, Ryckie G.; Glanvill, Louise; Wormald, Justin; Jain, Abhilash
Abstract: Optimal management of pedunculated ulnar polydactyly is not defined. This systematic review summarises objective and patient-reported outcomes following primary treatment. Two authors screened articles for inclusion according to a PROSPERO published protocol. The meta-analysis of adverse events was performed, and a narrative synthesis of satisfaction and patient-reported outcomes was reported. The risk of bias was assessed using Cochrane's ROBINS-I tool. Of 1650 articles identified, 15 were eligible, including 13 single-arm and 2 multi-arm studies. Complications were 6 times as likely with ligation procedures (22%), compared to surgical removal (1%) whether this was performed in the outpatient setting or operating theatre (OR 6.89 [95% CI 1.73, 27]). Parent-reported satisfaction was high for all treatments. Studies were at high risk of bias and low methodological quality. Outcome measurement and follow-up were heterogenous. Well-designed prospective observational and experimental studies are required to inform practice, incorporating clinician and parent-reported outcomes and economic analyses. Level of evidence: I.